2014
DOI: 10.1071/ah13154
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining supply of senior academic leadership skills in a shortage environment: a short review of a decade of dental experience

Abstract: For the past decade, and expected for the next decade, Australia faces a significant health workforce shortage and an acute maldistribution of health workforce. Against this background the governments at both national and state level have been increasing the training places for all health practitioners and trying to redress the imbalance through a strong regional focus on these developments. Dentistry has been an active participant in these workforce initiatives. This study examines the increasing demand for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In spite of this lack of evidence, a number of rural dental schools have been opened in Australia. It is essential that the working locations of graduates from rural and metropolitan dental schools be investigated, to determine whether the policy of opening rural schools is impacting on graduates’ choice of work location.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this lack of evidence, a number of rural dental schools have been opened in Australia. It is essential that the working locations of graduates from rural and metropolitan dental schools be investigated, to determine whether the policy of opening rural schools is impacting on graduates’ choice of work location.…”
Section: Introductionmentioning
confidence: 99%
“…Almost two decades ago it was predicted that retirements of dental school faculty would increase rapidly, 4 and that there would need to be sufficient numbers of academics in the next generation to fill this void. However, reported shortages of dental faculty remain a critical issue 5,6 . Similar crises have been identified in medicine, 7 nursing 8,9 and allied health 10 …”
Section: Introductionmentioning
confidence: 78%
“…On a global scale, there is a recognised shortage of dental leaders and dental school faculty to lead the dental industry into the future . Commentary in the Australian newspaper has identified that “vacancies at the head of six of Australia's 10 dental schools are creating a … crisis that requires urgent attention.” Further, an editorial in the Australian Health Review emphasises that developing visionary leadership is essential, if the dental profession is to address the ever‐changing oral health needs of the population …”
Section: Introductionmentioning
confidence: 99%
“…visionary leadership is essential, if the dental profession is to address the ever-changing oral health needs of the population. 4 There is very little evidence of dental schools offering formal leadership training for their students. 1,5 It is an area that is lacking, which is surprising given that undergraduate training would be an ideal time to enthuse and encourage the development of the dental leaders of the future.…”
mentioning
confidence: 99%